Globalization and the welfare state papers - Sodersten Bo ed.; Symposium on Globalization and the Welfare State; Symposium on globalization and the welfare state Jonkoping, Gt. Britain May/Jun 2002 (Hampshire Palgrave Macmillan, 2004)
DescriptionWith contributions from leading thinkers such as J. Bhagwati and Robert Solow, this edited collection examines some hotly debated issues in today's world. The significance of globalization and its effects on welfare states is discussed and analyzed. A special chapter is devoted to terrorism, and it is explained why some people are willing to sacrifice their lives to gain 'heavenly goods'. The role of multinationals in the globalization process is examined as is the importance of changing and evolving social norms regarding work and leisure for the survival of today's welfare states.
Keywords: Foreign trade and employment; Globalization-economic aspects; International economic relations; Welfare state